UPAYA STRATEGI PENINGKATAN KINERJA DAN KEBERLANJUTAN RANTAI PASOK AGROINDUSTRI KOPI ROBUSTA DI KABUPATEN TANGGAMUS - Seppa Septarianes; Marimin; Sapta Raharja (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
The supply chain activity of robusta coffee agroindustry in Tanggamus District involves several stakeholders, namely farmers, collectors, and KUB (Kelompok Usaha Bersama). Sustainable supply chain activities are economic, social, environmental and technological management activities. The objectives of the research were to analyse supply chain mechanism, to analyse supply chain value-added and performance, and to assess sustainable supply chain performance index of Robusta agroindustry performance. The stages of data processing were the identification of Robusta coffee supply chain agroindustry, value added analysis, measurement and assessment of supply chain performance indexes, and design of strategies to improve performance and supply chain sustainability in Robusta coffee agroindustry. The value added of robusta coffee agroindustry supply chain was analyzed using a modification of Hayami. SCOR-AHP (Supply Chain Operations Reference-Analytical Hierarchy Process) was used to measure performance. The sustainability status of Robusta coffee agroindustry was calculated using Multi-Dimensional Scaling (MDS) technique with R software. The value added ratio in farmers was lower supply chain actor (45.59%) compared to collectors (70.30%) and KUB (85.34%). The supply chain performance farmer performance was 70.99 lower than collector 87.14 and KUB 85.76. The sustainability of economic dimensions was almost sustainable (77.39), social dimensions were sustainable (88.24), environmental dimensions was almost sustainable (78.62), and technological dimensions was almost sustainable (66.67). The aggregating value of supply chain sustainable showed 77.71% which meant almost sustainable. This research recommends strategies to build coffee farmers’s partnerships with agroindustry to improve the performance and sustainability of Robusta coffee supply chain. Keywords: agroindustry, SCOR-AHP, robusta coffee, sustainability, supply chain